A Paging Training Program for a Fourth-Year Internship Readiness Course - Emily Cetrone (Association of American Medical Colleges, 2020)
Introduction New medical interns face a steep learning curve as they must manage complex medical scenarios, many of which they have only seen before in a classroom setting. To ameliorate these challenges, medical schools are increasingly including courses designed to address the transition from student to doctor. One of the biggest challenges for new interns is learning to triage and manage nursing pages, so we designed a mock paging program incorporated within our fourth-year transitions course. Methods We developed a database of clinical scenarios to occur via telephone between a nurse and a medicine intern. Throughout the 2-week course, these cases were administered to 40 fourth-year medical students by Master's level nursing students and nurse evaluators. The nurses used checklists to evaluate medical student management and communication, and at the end of the phone encounter students received immediate feedback. We used an observational prospective design, using a within subjects method with repeated measures. Results Data from a total of 216 phone calls were analyzed for 36 students. No statistically significant improvement of checklist scores was observed. Substantial interrater reliability was observed for the four observed cases with a Fleiss-Kappa of .76. Student comments indicated the activity was helpful for preparing them to answer pages. Discussion Our paging program offered students the chance to simulate being on call, as well as the opportunity to receive immediate feedback. It did not show improvement in checklists across time. Limitations included a small sample size and few common variables across the cases.